Perspectives of Armenia in Eurasian Economic Union - Jivanyan, D A (Vestnik Rossijskogo universiteta družby narodov. Seriâ Politologiâ (Online), 2015)
This article examines the problems and perspectives of post-soviet integration processes, on the example of Armenia’s accession to the Eurasian Union. The main political and economic grounds for Armenia’s accession to the Union are pointed out in the article. This research, through the elements of the method of SWOT analysis, reviews scenarios of possible developments around Armenia and the Eurasian Union. The author concludes that Armenia’s accession to the Eurasian Union is a mutually beneficial geopolitical, geostrategic step, which may promote the post-soviet integration processes.